Characterization of Optical Properties of Colloidal Gold Solution based on Changes in Concentration using Light Polarization Method - Winarno, Winarno; Firdausi, Ketut Sofjan; Soesanto, Qidir Maulana Binu; Khumaeni, Ali (Diponegoro University Semarang Indonesia, 2024)
This research was conducted to determine the effect of concentration on the characteristics of changes in the polarization angle of colloidal gold solutions. The method used in this research is natural polarization. The light source used was a green laser with a wavelength of 532 nm. The colloidal gold solution was obtained using the laser ablation method and then dissolved in aquabidest. The characteristics of changes in the angle of light polarization in the gold colloidal solution were obtained by varying the concentration of the gold colloidal solution (40 ppm, 30 ppm, 20 ppm, and 10 ppm). The results showed that gold colloids have optical activity because the orientation of the gold colloid molecules allows them to interact asymmetrically with linearly polarized light. In the range of concentration from 10 to 40 ppm, the polarization angle in gold colloids shows a linear pattern as a function of concentration. Within one month the colloidal gold sample showed stable properties. This method allows us to further analyze the quality of other types of colloids using the same method. This will improve our understanding of the interaction of polarized light with nanoparticles.